Kinematic analysis of maximal and sub-maximal snatch lifts in high level weightlifters - Diamantis, E.; Gourgoulis, V.; Garas, A.; Antoniou, P.; Aggeloussis, N. (Inquiries in Sport & Physical Education, 2016)
The purpose of this study was to investigate possible differences in the kinematic characteristics of maximal and sub-maximal snatch lifts. Two analog video cameras (60 Hz) were used to record the lifts of fourteen high performance level male weightlifters under competitive conditions. The three-dimensional kinematic analysis of the lifts was conducted using the Ariel Performance Analysis System (APAS). The snatch movement was divided into five phases: 1st pull, transition, 2nd pull, turnover and catch. These phases were determined according to the angular displacement of the knee joint and the vertical displacement of the barbell. The paired samples t-test was used for the statistical treatment of the data. The results revealed that during the maximal lifts, in comparison with the sub-maximal, the absolute and the relative duration of the 1st pull was longer, while the duration of the turnover phase was shorter. Moreover, the maximal height of the barbell was smaller, while its vertical displacement during the catch was greater. Smaller values were also observed in the vertical linear barbell`s velocity in the separate phases of the lift. The maximum angular extension of the shank and the thigh was greater in the maximal lifts, and as far as their extension velocity is concerned significant differences were found only in the extension velocity of the hip, which was faster during the sub-maximal lifts. Regarding the energetic characteristics of the barbell`s lift, significantly greater work during the 1st pull and significantly less power during the 2nd pull were observed in maximal lifts. Thus, although the general pattern of the movement remains unchanged during maximal and sub-maximal lifts, the different load causes some significant modifications in specific parameters of the lift.